TANGGUNG JAWAB HUKUM KEPALA DESA ATAS PEMALSUAN ALAS HAK DALAM PENDAFTARAN TANAH - Safitria, Esa Aprilia; Franciskab, Wira; Yania, Ahmad (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2024)
ABSTRACT (Font Cambria 10) Many cases that have been decided by the judicial institution related to the falsification of Land Certificates as the basis for land registration made by the village head have resulted in moral and material losses to the community. The purpose of this study is to analyze the legal standing and responsibility of the village head for falsifying the basis for making Land Certificates in the context of land registration. The Grand Theory of this study is the Theory of Legal Standing, while the applied theory uses the Theory of Legal Responsibility. The position of the Land Certificate as a private deed is a guide in the land registration process which functions as proof of physical control when the applicant does not have or is incomplete proof of control. Proof of initial ownership of land objects that are legitimate for residents in rural areas can be made into a Land Certificate issued by the local Village or Sub-district office. Forgery of the basis of the Land Certificate issued by the Village Head in land registration results in the issuance of a certificate of ownership containing legal defects, without a valid basis and incorrect legal data so that the certificate does not have binding legal force, and can be canceled by requesting cancellation at the State Administrative Court. Cancellation of a certificate of ownership as regulated in Article 1 number 14 of PMNA/KBPN Number 3 of 1999 is based on 2 (two) things, namely the decision contains administrative legal defects in its issuance or to implement a court decision that has permanent legal force. The village head who commits the act of falsifying a land certificate as the basis of rights in land registration must be responsible for his actions in the form of job responsibility and personal responsibility in the eyes of the law, both civilly, state administration, or criminally.